SEM approach to assess self-efficacy and social capital of producer’s organizations in Chhattisgarh - S K, JOSHI; R, UPADHYAY; A K, GAURAHA (The Indian Journal of Agricultural Sciences, 2024)
Farmer-producer organizations are typified by farmer groupings that are structured with the intention of turning a profit by leveraging economies of scale and functioning similarly to corporate entities. The creation and advancement of farmer collectivization can offer farmers a forum for obtaining essential information, exchanging knowledge, sharing production and marketing risks, and embracing market-driven agricultural product production. Compared to the individual method, grassroots initiatives on the collectivization of marginalized rural communities can enhance their support for livelihood in terms of income, self-respect, negotiating power, etc. The current study was carried out in the state of Chhattisgarh in order to propose a model by combining two schools of thought; the function of social capital, and self-efficacy that influence the perceived performance among the members of farmer producer organizations (FPOs). This study was set out to determine and investigate the fundamental causes of the farmers' groups' performance in producer businesses that are operating quite successfully on the ground. Findings reveal that self-efficacy was a key player as a partial mediator in the social capital formation that affected FPO performance. The size of mediating effect was analysed and observed highly significant with 45.77% effect size.